The Politics of the Two Qiblahs and the Emergence of an Alternative Islamic Monotheism - Eltigani Abdelgadir Hamid (International Institute of Islamic Thought, 2016)
Changing the prayer direction from Makkah to Jerusalem and then back to Makkah was probably one of the first Muslim community’s most contentious incidents. Due to its being highlighted in Q. 2:142-44, it has aroused an unending debate among Muslim exegetes, jurists, and western historians as to why the qiblah was changed. Was it based on a divine command or Muhammad’s independent judgment, a move to dilute the Arabs’ emotional attachment to the Ka‘bah, or a move to win over Madinah’s Jewish community? Might it have been a throwback to the Abrahamic heritage, envisaged by the Prophet as a base for a wider, monolithic Islamic nationalism? This article seeks to closely examine and clarify the “qiblah literature” in an attempt to reveal the Ka‘bah’s role not only as a geographical locale but also as a spiritual magnet, and to find out whether this incident represented a break or a continuation of an earlier strategy of socio-religious change.